Pelatihan Dan Penyuluhan Kewirausahaan Bagi Pelaku Usaha Dalam Meningkatkan Daya Saing Dan Inovasi - Kasim, Muhammad Yunus; Nurdin, Djayani; Darman, Darman; Fattah, Vitayanti; Asriadi, Asriadi; Buntuang, Pricylia Chintya Dewi; Evrianti, Hesti; Iskandar, Rizkiani; Utami, Ayu Putri (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Usaha Mikro, Kecil, dan Menengah (UMKM) di Indonesia menghadapi tantangan rendahnya adopsi teknologi digital dan terbatasnya kemampuan inovasi yang menghambat daya saing. Kegiatan pengabdian ini bertujuan meningkatkan pengetahuan dan keterampilan kewirausahaan melalui pelatihan terpadu bagi 100 peserta yang terdiri dari pelaku usaha UMKM, mahasiswa, dan alumni Universitas Tadulako. Metode pelaksanaan menggabungkan ceramah, workshop interaktif, dan praktik langsung selama 2 hari (11-12 September 2025) dengan materi meliputi strategi bisnis, pemasaran digital, pengelolaan keuangan, dan pengembangan inovasi produk. Evaluasi dilakukan melalui pre-test dan post-test menggunakan kuesioner terstruktur skala Likert. Hasil menunjukkan peningkatan signifikan pada keempat aspek: pemahaman strategi bisnis meningkat 50,3% dengan 67% peserta mencapai target; penguasaan pemasaran digital mencapai 76% peserta mampu mengoperasikan minimal 2 platform; kemampuan pengelolaan keuangan dicapai 73% peserta; dan 54% peserta menghasilkan ide inovasi produk. Pendekatan pembelajaran praktis menggunakan tools gratis seperti Excel, Canva, dan platform media sosial terbukti efektif meningkatkan kapasitas peserta. Pendekatan hybrid dan partisipatif dengan integrasi tools digital berbasis kebutuhan lokal belum banyak dikaji dalam pelatihan kewirausahaan di Indonesia, sehingga model ini menjadi kontribusi baru dalam konteks pendidikan kewirausahaan berbasis komunitas kampus yang dapat direplikasi untuk akselerasi literasi digital UMKM mikro. Keberhasilan program ini berkontribusi terhadap pencapaian SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), dan SDG 9 (Industry, Innovation and Infrastructure), serta memperkuat ekosistem kewirausahaan di lingkungan kampus. Entrepreneurship Training and Outreach for Business Actors to Enhance Competitiveness and Innovation Abstract Micro, Small, and Medium Enterprises (MSMEs) in Indonesia face significant challenges regarding low adoption of digital technology and limited innovation capabilities that hinder their competitiveness. This community service activity aimed to enhance entrepreneurial knowledge and skills through integrated training for 100 participants comprising MSME actors, students, and alumni of Tadulako University. The implementation method combined lectures, interactive workshops, and hands-on practice over 2 days (September 11-12, 2025), covering business strategy, digital marketing, financial management, and product innovation development. Evaluation was conducted through pre-test and post-test using structured Likert-scale questionnaires. Results demonstrated significant improvements across four aspects: business strategy comprehension increased by 50.3% with 67% of participants achieving the target; digital marketing proficiency reached 76% of participants capable of operating at least 2 platforms; financial management competency was attained by 73% of participants; and 54% of participants generated product innovation ideas. The practical learning approach utilizing free tools such as Excel, Canva, and social media platforms proved effective in enhancing participants' capacity. The hybrid and participatory approach with integration of digital tools based on local needs has not been widely studied in entrepreneurship training in Indonesia, making this model a novel contribution in the context of campus-based community entrepreneurship education that can be replicated for accelerating digital literacy among micro-MSMEs. The success of this programme contributes to the achievement of SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation and Infrastructure), whilst strengthening the entrepreneurial ecosystem within the campus environment.